A Furniture Design Guideline Derived from the Socio-Economic Factors of Consumers for Their Choices of Sustainable Furniture Design in Thailand - Karuna Kwangsawat; Yanin Rugwongwan (My University, 2017)
This article presents an environmentally friendly furniture design guideline which comes from different socio-economic conditions, including personality and physical residence of consumers in Thailand, and is a test for the perception of environmentally friendly furniture style, in order to find the style of environmentally friendly furniture in consumers with different economic backgrounds and perception of the environment. The research found that the needs for the style of environmentally friendly furniture according to different socio-economic conditions were in the same direction, which means that consumers need modern environmentally friendly furniture in western style, using natural materials in manufacturing with high technology, and furniture color in a cool shade. Therefore, the designer should consider the different socio-economic conditions of consumers that affect the needs differently, and use this as a furniture design guideline that is environmentally friendly and appropriate for the needs of consumers.
Keywords: Environmentally Friendly; Environmental Justice and Health Disparities